Seroprevalence of Bovine Adenovirus and Enterovirus Antibodies Reveals Different Infection Dynamics in Cattle Herds - Gras, Chris Kelli; Demolier, Meriane; Eisen, Ana Karolina Antunes; Spilki, Fernando Rosado; Hezel, Andréia (Acta Scientiae Veterinariae, 2017)
Background: Bovine enterovirus (BEV) and bovine adenovirus (BAV) are widely distributed in cattle population, and are among possible causes of gastroenteritis and respiratory disease, respectively, although the infection is more often subclinical. BAV infection may be also related to conjunctivitis, and may lead to severe infections and death in immunosuppressive calves. BEV infections have been associated with disorders of respiratory and reproductive tracts, and diarrhea. There is little available information about BAV and BEV in Brazil; however the main of the present study was to investigate the presence of antibodies against these viruses in cattle from some counties of the Rio Grande do Sul (RS), Brazil. Material, Methods & Results: A total of 415 bovine serum samples collected in 2015 year to detect neutralizing antibodies against BEV and BAV by Virus neutralization (VN) assay were performed. The serum samples were gently provided from Setor de Virologia da Universidade Federal de Santa Maria (SV-UFSM). The samples came from bovine with a history or report of clinical cases of diarrhea, respiratory and reproducible disorders and/or abortion suggestive of Leucosis, Bovine Viral Diarrhea Virus (BVDV) and/or Bovine herpesvirus type 1 and 5 (BoHV-1 and 5) infections. The samples are originated as from dairy and beef herd cattle in the following regions from RS State: Southwest, Northeast, Northwest, West, Southeast, Midwest and Metropolitan regions; and were classified according to the origin, gender and age. The serum samples were tested against 100 TCID50/mL of (tissue cellular infection dose 50/mL) of previously characterized BEV and BAV-3 isolates. Serial dilution of the serum was performed in duplicate, starting at 1:5 up to > 1:640 for BEV and at 1:2 to > 1:256 for BAV in 96 wells plates. The serum and virus mixture was incubated in 37ºC for 4-6 h and then a suspension of CRIB cells was added to each well. The plates were incubated in 37ºC and 5% CO2 for three days for BEV and five days for BAV assay. Neutralization titers were calculated as the reciprocal of the highest serum dilution able to avoid the cytopathic effect. A total of 99.7% (414/415) serum samples showed neutralizing antibodies to BAV and/or BEV. 99.2% (411/414) showed neutralizing antibodies against only BEV and 97.3 % (403/414) were seropositive only to BAV3. Regarding the sex of the analyzed population, males corresponded to 41.6% (173/415) and female 30.3% (126/415) of the total. From BEV seropositive samples, a higher frequency of neutralizing antibodies titers of 1:320, regarding 22.1% (91/411) of samples and for BAV-3 the titers > 1:256 were more prevalent, 72.2% (291/403) of seropositive. Discussion: The data in the present study showed that the frequency of neutralizing antibodies was high for both viruses as well as co-infection was prevalent; demonstrated that both viruses are actively circulating in the bovine population. However reinfections with BEV may be related to a higher proportion of animals presenting strong humoral immunity. Since BAV and BEV are normally related to subclinical infections, in the absence of clinical cases and high levels of herd immunity, it could be inferred that no other preventive measures need to be taken in these herds until no clear overt of clinical signs is noticed. In another hand, is important research these viruses in animals with signs historic of respiratory tract disease, reproductive disorders and diarrhea.